Analisa Kekerasan dan Struktur Mikro Sambungan Las Kampuh V Tunggal dan Kampuh V Ganda Pada Baja Karbon Rendah - Jusman, Jusman; Sudarsono, Sudarsono; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
The  development  of  production  technology  and  metal  raw  materials  cannot  be separated from the use of welding technology. So that it can be said that there is almost no metal that cannot be welded. Welding is a metal joining technique by partially melting the main metal and filler metal. The purpose of this study was to determine the hardness and microstructure of single v seam weld joint and double v seam welded on low carbon steel. In this study, using hardness testing methods and conducting microstructure observations to determine the structure formed in the  welding  results.  The  results  showed  that  the  micro  structure  of  the  single seam  v  was  dominated  by  pearlite  which  had  high  hardness  properties  with  an average value of hardness in the weld metal area of  142.80 kg / mm2, the HAZ area of  132.72 kg / mm2, and the area Main metal (Base Metal) is 121.46 kg / mm2,  while  the  double  seam  v  is  dominated  by  ferrite  which  has  low  hardness properties with an average value of weld metal (Weld Metal) of 125.80 kg / mm2, HAZ area of 121 , 20 kg / mm2, and the base metal area of 112.60 kg / mm2. Keywords : SMAW, Low Carbon, hem, hardness.